2016
DOI: 10.3892/ol.2016.5162
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of SUMO-specific protease 1 induces arsenic trioxide-mediated apoptosis by regulating XBP1 activity in human acute promyelocytic leukemia

Abstract: Small ubiquitin-like modifier (SUMO)/sentrin-specific protease 1 (SENP1), a member of the SENP family, is highly expressed in several neoplastic tissues. However, the effect of SENP1 in acute promyelocytic leukemia (APL) has not been elucidated. In the present study, it was observed that SENP1 deficiency had no effect on the spontaneous apoptosis or differentiation of NB4 cells. Arsenic trioxide (As2O3) could induce the upregulation of endoplasmic reticulum (ER) stress, resulting in the apoptosis of NB4 cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…M, DNA molecular weight markers; pXBP1U, unspliced XBP1 plasmid control; pXBP1S, spliced XBP1 plasmid control; 1:5, the ratio of pXBP1S plasmid to pXBP1U plasmid; and 5:1, the ratio of pXBP1S plasmid to pXBP1U plasmid Wang et al, 2019). Lastly, other posttranslational modifications, such as phosphorylation, acetylation/deacetylation and sumoylation/ desumoylation, can affect XBP1S protein stability and activity as well (Jiang et al, 2012;Lee et al, 2011;Liu et al, 2016;Wang et al, 2016;Wang, Chen, & Ouyang, 2011). These different mechanisms ensure that XBP1S is only produced and functional when it is needed during ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…M, DNA molecular weight markers; pXBP1U, unspliced XBP1 plasmid control; pXBP1S, spliced XBP1 plasmid control; 1:5, the ratio of pXBP1S plasmid to pXBP1U plasmid; and 5:1, the ratio of pXBP1S plasmid to pXBP1U plasmid Wang et al, 2019). Lastly, other posttranslational modifications, such as phosphorylation, acetylation/deacetylation and sumoylation/ desumoylation, can affect XBP1S protein stability and activity as well (Jiang et al, 2012;Lee et al, 2011;Liu et al, 2016;Wang et al, 2016;Wang, Chen, & Ouyang, 2011). These different mechanisms ensure that XBP1S is only produced and functional when it is needed during ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…These SUMOylation events signi cantly decrease the transcriptional activity of XBP1 towards UPR target genes [21]. While others showed that Sentrin/SUMO-speci c protease 1 (SENP1), a speci c de-SUMOylation protease for XBP1 can increase the transcriptional activity of XBP1 and ER stress-induced apoptosis through accumulating SUMOylated XBP1 [22,23]. Thus, we speculated that SUMOylation of XBP1 may regulate UPR activation and ER homeostasis in DCM.…”
Section: Introductionmentioning
confidence: 85%
“…A key transcription factor of the UPR. SENP1 regulated de-SUMOylation of XBP1 was involved in the ER stress-mediated apoptosis caused by arsenic trioxide treatment in NB4 cells (Wang et al, 2016).…”
Section: Xbp1mentioning
confidence: 94%
“…It was demonstrated that SENP1‐regulated specific de‐SUMOylation of XBP1 was correlated with ER stress‐mediated cell apoptosis caused by arsenic trioxide treatment in NB4 cells. These studies provided insights into potential therapeutic strategies for APL treatment via regulation of XBP1 signaling during ER stress by targeting SENP1‐mediated deSUMOylation of XBP1 (Wang et al, 2016).…”
Section: Sumoylation Of Proteins and Leukemiamentioning
confidence: 99%